Land of Forgotten Girls - Kelly, Erin Entrada (New York, NY Greenwillow Books, 2016)
Abandoned by their father and living in poverty with their heartless stepmother in Louisiana, two sisters from the Philippines, twelve-year-old Sol and six-year-old Ming, learn the true meaning of family.
Novel.
640L
Accelerated Reader AR
A Junior Library Guild Selection.
105889
Keywords: Dysfunctional families -- Juvenile fiction; Immigrants -- Louisiana -- Juvenile fiction; Sisters; Stepmothers; Filipino Americans; Family problems -- Fiction; Juvenile fiction -- Social Issues -- Emigration & Immigration; Juvenile fiction -- Family -- Siblings; Juvenile fiction -- Family -- Alternative Family; Louisiana -- Fiction; Domestic fiction; Fiction; Juvenile works; Curriculum resource